NOMADIC STATE OF THE KYRGYZ IN THE XVIII TO MID XIX CENTURY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The history of the Kyrgyz state in the XVIII-mid XIX centuries is one of the understudied issues in Kyrgyzstan’s history. In Soviet historiography, many states’ histories were poorly studied, often receiving a superficial treatment. Furthermore, the study of nomadic history was dominated by a Eurocentric perspective, wrongly suggesting that due to tribal structures, nomads, including the Kyrgyz, were unable to pursue unified state policies. However, as noted by the renowned Russian scholar Lev Gumilev, nomadic culture had its own path of development and was not peripheral or primitive [28:94]. This paper aims to address these issues in Kyrgyz historiography and shed light on the past nomadic community, which remains insufficiently explored to this day.
Keywords: Wild Mountain Kyrgyz Ordo, Bukhara Emirates, Kazakh Zhuses, Kyrgyz government, Kokand, Ordo, Russia